Practical experiences of digitalization and automation in logistics - Fükő, László; Váci, Gergely; Lukács, Adrienn; Hegedűs, Zoltán; Mindszenti, Csilla; Menyhért, Anita; Cservenák, Ákos; Tamás, Péter (Advanced Logistic Systems - Theory and Practice, 2024)
Recently, digitalization and automation have gained more and more space, which has long been felt in the field of logistics. Although we can find examples of both in almost every major company, we can state that each company uses them to a different extent and in different areas. In addition to the fact that we find many different examples, it is typical that they are specifically customized and therefore their introduction requires additional expenditures and changes at other companies. What can and to what extent is it reasonable to digitize and automate? What are the prerequisites for these to be implemented cost-effectively and in the most targeted manner